Analysis of Vegetative Morphological Characteristics, Yield Potential, and Chemical Composition of Sweet Potato Lines (Ipomoea batatas L.) Resulting from Open Pollination with Ayamurasaki Female Parents - Binsar Simarmata; Ratna Dewi; T. Imam Sofi'i (Biology, Medicine, & Natural Product Chemistry, 2026)
Sweet potato (Ipomoea batatas L.) is an important food crop in Indonesia with high potential to support food diversification, improve nutrition, and develop functional food products. The purple-fleshed variety (Ayamurasaki) is used as the female parent in breeding programs due to its high anthocyanin content. This study aimed to analyze the vegetative morphological characteristics, yield potential, and chemical composition of open-pollinated sweet potato lines using Ayamurasaki as the female parent. This study was conducted using a Randomized Block Design (RBD) consisting of five lines, namely A19, A23, A39, A74, A84, and the Ayamurasaki variety as a control, with three replications. Observations were made on vegetative morphological parameters, tuber weight per plant, and chemical composition analysis. The results showed significant variations among the tested genotypes for all observed parameters. The A23 line showed superior performance, characterized by larger leaf size, larger stem diameter, high yield, and the highest anthocyanin content. Meanwhile, the A84 line showed potential for industrial use due to its relatively high carbohydrate and starch content. These findings provide valuable information for the further development of superior sweet potato lines with high productivity and better nutritional value to support future breeding programs.